Factors Affecting Green Purchase Intention and its Impact on Green Purchase Behavior - Nazmi, Muhamad Ibnu; Kurniawati, Kurniawati (Universitas Pendidikan Indonesia, 2024)
This study aims to obtain empirical evidence related to the influence of factors affecting green purchase intention. In addition, this study also examines the effect of green purchase intention on green purchase behavior moderated by willingness to pay. The data analysis method uses Structural Equation Modeling (SEM) AMOS. This research is quantitative research using primary data and obtaining 162 respondents. The results showed that green brand knowledge, environmental concern, and green perceived value have a positive effect on green purchase intention. Meanwhile, environmental knowledge does not affect green purchase intention. In addition, green purchase intention and the moderating role of willingness to pay can strengthen the influence of green purchase intention on green purchase behavior. This research also provides implications for further research, consumers, and companies. The novelty in this research is the addition of willingness to pay as a moderating variable.